A Case Report of Sequela of Operation of Talus Osteonecrosis - Choi Sung-Hun; Kim Kyung-Un; Lee Yoon-Kyoung; Lee Kyung-Min; Lim Seong-Chul; Jung, Tae-Young; Seo, Jung-Chul (Korean Pharmacopuncture Institute, 2006)
Objective : The clinic study or report about Oriental Medical treatment about osteonecrosis is very insufficient. Therefore, we report a case about a sequela of operation of talus osteonecrosis treated by Oriental Medical treatments. Methods : The patient was managed by bee venom and Carthami Flos Herbal-Acupuncture, Sa-am and body acupucture, oxibustion, physical theraphy and herbal medicine. We evaluated the patient through Visual Analogue Scale(VAS). Results : After 25 days of treatment, the patient showed that clinical symptoms was decreased and VAS changed from 10 to 2. Conclusion : In this case, Oriental Medical treatments for a sequela of operation of talus osteonecrosis was effective. But further studies are required to confirm the effect of these methods